Innovative self strengthening reinforced concrete beam / Muhammad Arif Ikmal Abdul Halim ... [et al.] - Abdul Halim, Muhammad Arif Ikmal; Lyn Dee, Goh; Ahmad Zakwa, Fariz Aswan; Ismail, Clotilda; Petrus, Clotilda (2022)
Concrete structures deteriorate over time, regardless of the workmanship, natural disasters, concrete lifespan, or overloading structures beyond their initial design load. To overcome this dilemma, additional materials may be installed at the critical stress area of the beam’s cross-section to increase the strength of a weakened reinforced concrete (RC) beam structure. One of the most common methods to strengthen the RC beam is by using prestressing force. In RC beams, prestressing helps to minimise existing deformations and crack occurrences. However, conventional prestressing techniques require specialised hydraulic jacking and anchorage systems, which may not be feasible in certain situations. Shape memory alloy (SMA) has the ability to recover its original shape upon deflection by heating. Therefore, the initial stress forces could be introduced into the RC beam to increase its capability without the need of jacking tools. This project aims to propose a self-strengthening RC beam. A 3D finite element model using ABAQUS software was executed and subjected to a four-point bending test. The result showed that the self-strengthening RC beam obtained an increment of 30% in load capacity compared to conventional beam.